Asuhan Kebidanan Komprehensif NY. Y dengan KEK dan CPD di BPM NY. S Puskesmas Kaliwadas - Sindi Khumaeida; Hafsah Hafsah; Sri Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Background : The maternal mortality rate in the world is about 303,000 out of 91.45/100,000 KH (WHO, 2022). In ASEAN, the maternal mortality rate in developing countries is 250 per 100,000 (ASEAN Secretariat, 2022). In Indonesia, the maternal mortality rate in 2022 is 183/100,000 KH (Indonesian Ministry of Health, 2022). In Central Java Province, the maternal mortality rate in 2022 was 76,93/100,000 KH (Central Java Health Office, 2022). In Brebes Regency, the maternal mortality rate in 2022 was around 105 cases (Brebes Health Office, 2022). Kaliwadas Health Center in 2022 recorded 1 case of maternal mortality (Health Profile of Kaliwadas Health Center in 2022). Objective : Provide comprehensive midwifery care for pregnant women, maternity, newborns, postpartum and family planning (KB) using the Varney and SOAP management approaches. Research Methods: The method used in this research is a qualitative descriptive method with a comprehensive case study approach. Results : Pregnancy midwifery care that has been given to Mrs. Y aged 20 years with Chronic Energy Deficiency and CPD has been given management according to the needs of the mother, In labor, newborn, postpartum until family planning Mrs. Y did not have complications and there were no gaps between theory and practice. Conclusion: Comprehensive midwifery care given to Mrs. F with Chronic Energy Deficiency (SEZ) and CPD has been carried out in accordance with Standard Operating Procedures (SOP) with the condition of the mother and baby is good.